SARANA PENJAMIN KREDIT DAERAH (SPKD) MENUJU MASYARAKAT SEJAHTERA 2015 - Desy Apriliani, Putu (INPUT Jurnal Ekonomi dan Sosial, 2008)
Is it believe that one of the efforts to reduce the poverty as well as the achievement of the goal of MDGs is creating the active participation of poor people itself in every part of initiative that is aimed to achieve the goal. To push the expance and opportunity of the poor people in business is setted to gain the con? dence of poor people to relie? ng their poorness. The opportunity could be in the form of developing the condusive condition for the Small and Medium Enterprises (SMEs) growth in example better access to the source of capital. Nowadays, a better access of SMEs to ? nancial institutions is facilitated by the guarantee system called Sarana Penjamin Kredit Daerah (SPKD) that being ? rstly owned by the government of Denpasar District among all regencies in Bali. Through SPKD, hopefully the loan disbursement of SMEs will increase; as well as the productivity, and at last creating a better standard of living of the poor people